On Mixed Quermassintegral for Log-Concave Functions - Fangwei Chen; Jianbo Fang; Miao Luo; Congli Yang (Journal of Function Spaces)
In this paper, the functional Quermassintegral of log-concave functions in ℝn is discussed. We obtain the integral expression of the ith functional mixed Quermassintegral, which is similar to the integral expression of the ith mixed Quermassintegral of convex bodies.